Developing of World Class Company's Differentiated Competitive Advantage through Human Capital Development - Sihombing, Haeryip; Yaakob, Mohd Yuhazri; Safarudin, Mochamad (Program Magister Manajemen Fakultas Ekonomi, Universitas Samratulangi Manado, 2011)
In the era of globalization, competitive advantage is a strategy of companies to survive in the hyper-competitive market. On how the company to success in the business, they should therefore explore their owned uniqueness of competitive advantage. The purpose of this paper is to review the challenges faced in developing strategies of competitive advantage by adapting and finding the solution in integrating of the human capital concepts. Based on traps in the business and what action required as well as concepts of lean and Japanese culture to the system approaches, their relevancy as a differentiator of competitive advantage toward human capital is reviewed. Through Fit Management, the paper also review the performance challenges and measurements systems to help the companies enhancing their capabilities by continuously and effectively identifying and eliminating the waste regarding human capabilities, besides the initiatives and creativities for innovation.